Transport properties of polymer-vapour grown carbon fibre composites - Gordeyev, S. A. (2000)
DC electrical resistivity and thermal conductivity of polypropylene (PP) filled with vapour grown carbon fibre (VGCF) was studied. This was done for a wide range of fibre content and compared to systems produced under the same conditions in which a conventional carbon fibre was used as filler. The composites studied exhibit characteristic percolating behaviour. Because of the low degree of graphite perfection in the VGCF used in this work, the fraction of VGCF required to achieve percolation was higher than expected. Non-linear I-V characteristics and time dependent electrical resistivity effects are only observed in PP filled with VGCF. Several mechanisms must be called upon to explain the observed electrical behaviour of the PP/VGCF composite. The thermal conductivity of the composites is in agreement with the effective medium theories.